2007
DOI: 10.4269/ajtmh.2007.77.203
|View full text |Cite
|
Sign up to set email alerts
|

Medicine Sellers and Malaria Treatment in Sub-Saharan Africa: What Do They Do and How Can Their Practice Be Improved?

Abstract: Medicine sellers are widely used for fever and malaria treatment in sub-Saharan Africa, but concerns surround the appropriateness of drugs and information provided. Because there is increasing interest in improving their services, we reviewed the literature on their characteristics and interventions to improve their malaria-related practices. Sixteen interventions were identified, involving a mixture of training/capacity building, demand generation, quality assurance, and creating an enabling environment. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
291
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(308 citation statements)
references
References 68 publications
11
291
0
Order By: Relevance
“…The more successful of these involved the drug vendors in the design and content of training, and found that gaining the trust and commitment of informal private providers was extremely important to the program's success, because they operate largely outside the government regulatory framework and can be suspicious of external attention. Our findings support those discussed in a recent review of the role of medicine sellers in malaria treatment by Goodman and others, 9 namely that successful interventions included buyin from medicine sellers and community members, use of a combination of approaches (including visual job aides such as dosing charts and community sensitization), and maintenance of training and supervision. Informal private providers, such as drug vendors and general shopkeepers, are widely used for fever and malaria treatment in sub-Saharan Africa, often forming the first (and in some cases, only) source of care.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The more successful of these involved the drug vendors in the design and content of training, and found that gaining the trust and commitment of informal private providers was extremely important to the program's success, because they operate largely outside the government regulatory framework and can be suspicious of external attention. Our findings support those discussed in a recent review of the role of medicine sellers in malaria treatment by Goodman and others, 9 namely that successful interventions included buyin from medicine sellers and community members, use of a combination of approaches (including visual job aides such as dosing charts and community sensitization), and maintenance of training and supervision. Informal private providers, such as drug vendors and general shopkeepers, are widely used for fever and malaria treatment in sub-Saharan Africa, often forming the first (and in some cases, only) source of care.…”
Section: Discussionsupporting
confidence: 79%
“…Recent reviews have provided information on the factors that influence treatment seeking behavior 7 and behavior of certain categories of healthcare providers, [8][9][10] but to date no over-arching comparison has been made of the relative effectiveness of the various interventions to improve these behaviors or their resulting impact on the diagnosis and effective treatment of patients with malaria within the first day of their illness. If we want to reach the RBM targets, we first need to identify those interventions that are most successful at improving access to prompt and effective malaria diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although a prescription is often legally required for selling misoprostol or mifepristone, sale of drugs without prescription is common in many LMICs (Goodman et al. 2007). Although studies show that MA is safe, effective, and easily self‐administered in low‐resource settings (Harper et al.…”
mentioning
confidence: 99%
“…7 The high persistence of substandard artemisinin combined therapies (ACTs) and inappropriate artemisinin monotherapies in the private sector, especially in sub-Saharan Africa (where many individuals buy their treatments privately), risks patient safety, and through drug resistance, places the future of malaria treatment at risk globally. [8][9][10][11] Several of these ACTs are currently available in Côte d'Ivoire, where ASAQ and AL combinations are common.…”
Section: Introductionmentioning
confidence: 99%